Study and Analysis of Performance of a Commercial Grid-Connected Rooftop Solar PV Plant - Balaji, C; Sahai, Shikhar; Jha, Subham; Sakthi, S; Mukherjee, Baishali; Dominic Savio, A; Chakraborthi, Abhishek (International Journal of Engineering and Technology, 2018)
This paper analyzes the performance of a rooftop solar PV plant installed in Chandigarh, India. The generation data of the grid-connected plant was collected via remote monitoring and was used to calculate the performance parameters like Performance Ratio and Capacity Utilization Factor using many other parameters as defined in international standards, like different yields, were also calculated. These parameters have then been compared with those obtained from simulations performed for the same plant. HelioScope was used to estimate the performance parameters mentioned using meteorological and solar radiation resource data. Various other parameters and losses related to the plantâ€™s performance have been reported graphically and have been studied and analyzed. Hypothesis testing using P90 and P50 analysis has been carried out to report the statistical significance of PV generation estimated from commercial softwares.Â Â